Pengaruh Pengetahuan Dan Sikap Ibu Hamil Serta Peran Bidan Terhadap Pola Konsumsi Mineral Pada Ibu Hamil Di Wilayah Puskesmas Banyumas - Ida Puspitasari; Dyah Umiyarni Purnamasari; Elviera Gamelia (JURNAL NUTRISIA, 2016)
Background: The mother's health condition before and after the very pregnant determines the health of pregnant women. So for the sake of the success of the pregnancy, the mother's nutritional state at the time of conception must be in good condition, and during pregnancy should get an extra energy, protein, vitamins, and minerals. The State of health of pregnant women depends on the patterns of everyday food that can be determined by the quality and quantity of the dishes. According to l. Behavioral health is influenced by three factors, namely predisposing factors (knowledge, attitude, belief, education and social levels), factor endowments (health facilities and infrastructure, and the availability of nutritious food), and the amplifier (the role of family, friends, teachers and health workers). Therefore need to do analysis on the influence of the knowledge and attitude to pregnant women as well as the role of the midwife's response to dietary minerals (iron, calcium, and iodium) on pregnant women in work-area Clinics Banyumas Objective: The purpose of this study was to determine the influence of knowledge and attitude of pregnant women and the role of midwife to the consumption patterns of minerals (iron, calcium, and iodine) in pregnant women. Methods : This research is quantitative research survey approach using the analytic cross-sectional study design. The research was conducted in June - Juli of 2015 at the Banyumas Primary Health Center with a sample of 80 people selected by simple random sampling. Data was collected using a questionnaire and food frequency questionnaire and then conducted data analysis of bivariate, and multivariate analyzes. Results : using bivariate chi-square analysis showed that factors associated with mineral consumption patterns in pregnant women is knowledge (p = 0.013). The factors that are not related to mineral consumption patterns in pregnant women is the attitude (p = 0.072) and the role of midwife (0,113). Multivariate analysis using logistic regression showed that the most influential factor on the consumption patterns of minerals in pregnant women is knowledge (Exp (B) = 3.462). Conclusion : It is recommended to pregnant women to increase her knowledge in order to increase mineral consumption patterns. Keywords : Knowledge, Attitude, Midwife, Mineral